Improving Critical Thinking Skills of Class VI Students Building Space Materials through the RME Learning Model - Mariani, Sri; Nurasiah, Iis; Nurmeta, Irda Khaleda (Lembaga Penelitian dan Pendidikan Mandala, 2024)
This research aims to describe efforts to improve critical thinking skills in building materials by implementing the learning model of realistic mathematics education (RMEl) at SDN Cijambe Tengah Sukaresmi Village, Cisaat District, Sukabumi Regency for the 2023/2024 academic year in the school year. The research method used is Class Action Research (PTK) with The research design uses the Kelmmis and Mc Taggart model which is carried out in two cycles. Each cycle consists of planning, implementation, action and observation, as well as reflection. Participants in this research are 35 class VI students. This research data collection technique uses a type of test. preltelst and polstelst. The initial research techniques take the form of observation, field notes and documentation. The data analysis technique used is descriptive quantitative. In the pre-cycle, this activity still uses the colonial learning model. Students' mathematical critical thinking skills improve after implementing the RMEl learning model. This can be seen from the learning completion of classically educated students who have experienced an increase. Starting with the pre-cycle where this activity still uses the national learning model, namely 29% or 10 students who completed above the KKM (70) out of a total of 35 students. Then, carrying out the first cycle stage by implementing the RM learning model, the ability to think critically in mathematics resulted in an increase in the total level of 49% or 17 students who completed the KKM, then the research continued with the second cycle stage until they achieved a total completion score of 74% or as many as 26 students who completed the KKM. Therefore, the research was stopped classically because it had reached or exceeded the 70% achievement indicator.This research aims to describe efforts to improve critical thinking skills in building materials by implementing the learning model of realistic mathematics education (RMEl) at SDN Cijambe Tengah Sukaresmi Village, Cisaat District, Sukabumi Regency for the 2023/2024 academic year in the school year. The research method used is Class Action Research (PTK) with The research design uses the Kelmmis and Mc Taggart model which is carried out in two cycles. Each cycle consists of planning, implementation, action and observation, as well as reflection. Participants in this research are 35 class VI students. This research data collection technique uses a type of test. preltelst and polstelst. The initial research techniques take the form of observation, field notes and documentation. The data analysis technique used is descriptive quantitative. In the pre-cycle, this activity still uses the colonial learning model. Students' mathematical critical thinking skills improve after implementing the RMEl learning model. This can be seen from the learning completion of classically educated students who have experienced an increase. Starting with the pre-cycle where this activity still uses the national learning model, namely 29% or 10 students who completed above the KKM (70) out of a total of 35 students. Then, carrying out the first cycle stage by implementing the RM learning model, the ability to think critically in mathematics resulted in an increase in the total level of 49% or 17 students who completed the KKM, then the research continued with the second cycle stage until they achieved a total completion score of 74% or as many as 26 students who completed the KKM. Therefore, the research was stopped classically because it had reached or exceeded the 70% achievement indicator.ellitian ini berltujuan melndelskripsikan upaya peningkatan keterampilanberpikirkritismateribangun ruangdenganpenl elrapan modl ellpelmbellajaranrelalistic mathelmaticselducatioln(RMEldiSDN CijambeTengahDesaSukaresmiKecamatanCisaatKabupatenSukabumi tahun pellajaran 2023/2024 diselmelstelr gelnap. Meltoldel pelnellitian yang digunakanadalahPenl ellitianTindakan Kellas(PTK) delngan delsain pelnellitian melnggunakan modl ell Kelmmis dan Mc Taggartyangdilakukanselbanyakduasiklus.Seltiapsiklus terldiridari pelrenl canaan, pellaksanaan, tindakan dan pelngamatan, serlta relflekl si. PartisipandalampelnellitianiniadalahpelselrtadidikkelasVI selbanyak 35siswa.Telknikpelngumpulandatapenl ellitianinimelnggunakantels belrupa pretlelst dan polstelst. Seldangkan tekl nik noln tesl belrupa obl serlvasi, catatan lapangan dan dolkumelntasi. Telknik analisis data yangdigunakanadalahkuantitatifdelskriptif.Padaprasiklusdimana pada kegl iatan ini masih melnggunakan moldell pelmbellajaran kolnvelnsiolnal. Keterampilan berpikir kritis matelmatika siswa melningkat setlellah melnerlapkan moldell pelmbellajaran RMEl. Hal ini dapat dikeltahuidariketluntasanbellajar pelserlta didik secl ara klasikal yangmelngalamipelningkatan.Diawalidelnganprasiklusdimanapada kelgiataninimasihmelnggunakanmodl ellpelmbellajarankolnvelnsiolnal yaituselbeslar29%atau10pelselrtadidikyangtuntas diatasKKM (70) daritoltaljumlahkeslelluruhan35siswa.Kelmudiandilakukantahapan siklusIdenl ganmelnerlapkanmodl ellpelmbellajaranRMElkelmampuan berpikirkritismatelmatikamelngalamipelningkatanselbelsar49%atau 17siswa yangtuntasKKM,makapelnellitiantetlapdilanjutkankeltahap siklus II sampai melmpelrollelh nilai keltuntasan selbelsar 74% atau selbanyak 26 siswa yang tuntas KKM. Ollelh selbab itu, pelnellitian dihelntikan selcara klasikal karenl a tellah melncapai atau mellelbihi indikatorl ketlerlcapaian70%.xjucThisresearchaimstodescribeeffortstoimprovecriticalthinkingskillsinbuildingmaterialsbyimplementingthelearningmodelofrealisticmathematicseducation(RMEl)atSDNCijambeTengahSukaresmiVillage,CisaatDistrict,SukabumiRegencyforthe2023/2024academicyearintheschoolyear.TheresearchmethodusedisClassActionResearch(PTK)withTheresearchdesignusestheKelmmisandMcTagg